Morphine modulation of pain processing in medial and lateral pain pathways - Woodward Donald J; Chang Jing-Yu; Huang Jin; Wang Jin-Yan; Luo Fei (Molecular Pain, 2009)
Abstract Background Despite the wide-spread use of morphine and related opioid agonists in clinic and their powerful analgesic effects, our understanding of the neural mechanisms underlying opioid analgesia at supraspinal levels is quite limited. The present study was designed to investigate the modulative effect of morphine on nociceptive processing in the medial and lateral pain pathways using a multiple single-unit recording technique. Pain evoked neuronal activities were simultaneously recorded from the primary somatosensory cortex (SI), ventral posterolateral thalamus (VPL), anterior cingulate cortex (ACC), and medial dorsal thalamus (MD) with eight-wire microelectrode arrays in awake rats. Results The results showed that the noxious heat evoked responses of single neurons in all of the four areas were depressed after systemic injection of 5 mg/kg morphine. The depressive effects of morphine included (i) decreasing the neuronal response magnitude; (ii) reducing the fraction of responding neurons, and (iii) shortening the response duration. In addition, the capability of cortical and thalamic neural ensembles to discriminate noxious from innocuous stimuli was decreased by morphine within both pain pathways. Meanwhile, morphine suppressed the pain-evoked changes in the information flow from medial to lateral pathway and from cortex to thalamus. These effects were completely blocked by pre-treatment with the opiate receptor antagonist naloxone. Conclusion These results suggest that morphine exerts analgesic effects through suppressing both sensory and affective dimensions of pain.